7+3=(x-4)

Simple and best practice solution for 7+3=(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3=(x-4) equation:



7+3=(x-4)
We move all terms to the left:
7+3-((x-4))=0
We add all the numbers together, and all the variables
-((x-4))+10=0
We calculate terms in parentheses: -((x-4)), so:
(x-4)
We get rid of parentheses
x-4
Back to the equation:
-(x-4)
We get rid of parentheses
-x+4+10=0
We add all the numbers together, and all the variables
-1x+14=0
We move all terms containing x to the left, all other terms to the right
-x=-14
x=-14/-1
x=+14

See similar equations:

| 14r+6=2(5+7r)-4 | | -9=3x/2 | | -x-3+3x=-1 | | 6/7x=1/2 | | m+7m=5+7m-7-5 | | 9=1/2(-2+5n) | | 15(b-2)=90 | | -4/9x=-36 | | 56z=35 | | 25(x-1)^2=49 | | -9/5x=-45 | | 300=0.02v^2+1.2v | | 3+y/3=-1 | | 4(2+x)1=7x-3(x-2) | | 2.5-0.02x=0.08 | | q/6=20 | | (3x+2)+(3x+2) = 8x−2 | | (3x+28)=4(x-10) | | -2x+10=-2(x+5 | | 2y=3.75 | | 12g=12(​3/​2​​g−1)+11 | | (x+5)2=10x | | 2/9d+1/9d=3 | | (3x+2)+(3x+2) =8x-2 | | 11÷5b+2=3÷5b+10 | | 3x+(2x+5)+(2x+10)+(2x-15)=360 | | x^2+60x-15000=0 | | 8x-4=3x-21 | | (3.7x)-7.61=8.3 | | 1-3m=-5 | | (3+x)=3(x-3)-4 | | x=-11/13 |

Equations solver categories